The canon or canons of values contained in the statutes of contemporary Polish political parties - Kępka, Izabela; Warda-Radys, Lucyna (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article proposes a look at the world of values in the statutes of political parties on two levels determined by S. Niebrzegowska-Bartmińska: communication (interaction) and performance. The former is related to the sender, recipient, intention and communication situation, the latter — is clearly verbalized, showing the most important values for the sender. The value at the interactive level in the statutes of political parties is considered to be universal good: creating an institutional unity of action for the benefit of the supra-individual. Values important for political parties that appear at the level of representation are very similar to each other and, in fact, independent of the party’s slant. The differences in the statutes concern rather small things, a slightly different formulation of similar content, or a more or less detailed treatment of various issues.